2022
DOI: 10.1007/s00167-022-07281-z
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps tendon autograft with or without bone block have comparable clinical outcomes, complications and revision rate for ACL reconstruction: a systematic review

Abstract: Purpose The purpose of this systematic review is to report complications, graft failure, fixation methods, rehabilitation protocol, clinical and patient-reported outcomes, and return to sports with the use of quadriceps tendon graft with the bone block (QT-B) and without bone block (QT-S). Methods According to the PRISMA guidelines a comprehensive search was performed across PubMed/MEDLINE, Scopus, EMBASE, and Cochrane Library databases from inception unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…Despite these differences, a recent systematic review compared the use of the QT graft with or without a bone fragment and showed that both grafts are safe and viable, with comparable clinical results, complications and revision rates. 51 Furthermore, QT graft can be used with partial or full thickness, with no difference between them in a recent systematic review. 52 When compared to other graft options, the QT graft has benefits such as lower morbidity at the donor site (defined as anterior knee pain, difficulty or inability to kneel or both) when compared to the patellar tendon autograft.…”
Section: Autologous Quadricipital Tendon Graftmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these differences, a recent systematic review compared the use of the QT graft with or without a bone fragment and showed that both grafts are safe and viable, with comparable clinical results, complications and revision rates. 51 Furthermore, QT graft can be used with partial or full thickness, with no difference between them in a recent systematic review. 52 When compared to other graft options, the QT graft has benefits such as lower morbidity at the donor site (defined as anterior knee pain, difficulty or inability to kneel or both) when compared to the patellar tendon autograft.…”
Section: Autologous Quadricipital Tendon Graftmentioning
confidence: 99%
“…Apesar dessas diferenças, uma revisão sistemática recente comparou a utilização do enxerto TQ com ou sem fragmento ósseo e mostrou que ambos os enxertos são seguros e viáveis, com resultados clínicos, complicações e taxa de revisão comparáveis. 51 Além disso, o enxerto TQ pode ser utilizado com espessura parcial ou total, sem diferença entre eles em revisão sistemática recente. 52…”
Section: Enxerto Autólogo Do Tendão Quadricipitalunclassified
See 1 more Smart Citation
“…In contrast, the deep portion has an avascular area of 10 mm proximal to the border of the patella, measuring approximately 30 mm × 15 mm. [6] Fig. 1 Anatomy of the quadriceps femoris muscle in frontal and sagittal view…”
Section: Anatomical and Mechanical Considerationmentioning
confidence: 99%
“…11 Graft choice for the ACL reconstruction influences the clinical outcomes, graft rupture, and complications. 12,21 Therefore, the appropriate choice of graft is an essential part of ACL reconstruction.…”
mentioning
confidence: 99%